2000
DOI: 10.1111/1469-8986.3740440
|View full text |Cite
|
Sign up to set email alerts
|

Selective slow‐wave sleep deprivation and time‐of‐night effects on cognitive performance upon awakening

Abstract: We evaluated the effects of selective slow-wave sleep (SWS) deprivation and time-of-night factors on cognitive performance upon awakening. Ten normal men slept for 6 consecutive nights in the laboratory: 1 adaptation, 2 baseline, 2 selective SWS deprivation, and 1 recovery night. Cognitive performance was assessed by means of a Descending Subtraction Task after 2, 5, and 7.5 h of sleep. There was an almost complete selective SWS suppression during both deprivation nights, and a significant SWS rebound during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 11 publications
(17 reference statements)
3
18
0
Order By: Relevance
“…Previous studies of experimental SWS suppression have focused on subjective sleepiness and measures of cognitive performance and have suggested that SWS may be important for waking neurobehavioral function (1,16). In the present study, we were able to induce a selective and profound reduction in SWS and to observe a clear adverse impact on daytime glucose tolerance with a clear increase in a well validated marker of diabetes risk.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies of experimental SWS suppression have focused on subjective sleepiness and measures of cognitive performance and have suggested that SWS may be important for waking neurobehavioral function (1,16). In the present study, we were able to induce a selective and profound reduction in SWS and to observe a clear adverse impact on daytime glucose tolerance with a clear increase in a well validated marker of diabetes risk.…”
Section: Discussionsupporting
confidence: 50%
“…Previous research has demonstrated a relationship between poor sleep quality and impaired performance, [6][7][8][37][38][39] yet here, caffeine resulted in higher accuracy scores on the n-back task relative to placebo. The most likely explanation for this unexpected finding is that residual caffeine may have directly ameliorated some of the effects of poor sleep.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, Ryman et al (1985) reported that 3 h of sleep after only 17 h of continuous work did not improve performance. Other studies have concluded that 1-2 full nights of sleep are needed to recover cognitively from sleep loss due to sleep fragmentation or partial sleep deprivation (Bonnet and Arand, 1998;Ferrara et al, 2000;Dinges et al, 1997).…”
Section: Introductionmentioning
confidence: 99%